The unquiet dead eaudiobook A novel. - Khan, Ausma Zehanat (HighBridge Audio, 2015)
Despite their many differences, Detective Rachel Getty trusts her boss, Esa Khattak, implicitly. But she's still uneasy at Khattak's tight-lipped secrecy when he asks her to look into Christopher Drayton's death. Drayton's apparently accidental fall from a cliff doesn't seem to warrant a police investigation, particularly not from Rachel and Khattak's team, which handles minority-sensitive cases. But when she learns that Drayton may have been living under an assumed name, Rachel begins to understand why Khattak is tip-toeing around this case. It soon comes to light that Drayton may have been a war criminal with ties to the Srebrenica massacre of 1995. If that's true, any number of people might have had reason to help Drayton to his death, and a murder investigation could have far-reaching ripples throughout the community. But as Rachel and Khattak dig deeper into the life and death of Christopher Drayton, every question seems to lead only to more questions, with no easy answers. Had the specters of Srebrenica returned to haunt Drayton at the end, or had he been keeping secrets of an entirely different nature? Or, after all, did a man just fall to his death from the Bluffs?